Design and Baseline Data for a Prospective Observational Study of Rivaroxaban in Patients with Venous Thromboembolism in Japan (XASSENT) - Fukuda, Ikuo; Hirayama, Atsushi; Kawasugi, Kazuo; Kobayashi, Takao; Maeda, Hideaki; Nakamura, Mashio; Nakanishi, Norifumi; Yamada, Norikazu; Tajima, Tsubasa; Iwashiro, Sanghun; Okayama, Yutaka; Sunaya, Toshiyuki; Hirano, Kazufumi; Hayasaki, Takanori (TH Open, 2021)
Background The efficacy and safety of rivaroxaban have been demonstrated in phase 3 trials of patients with venous thromboembolism (VTE; pulmonary embolism [PE] and deep vein thrombosis [DVT]). Data regarding rivaroxaban treatment of VTE in routine Japanese clinical practice remain limited.Objectives XASSENT will evaluate rivaroxaban treatment of VTE in real-world Japanese clinical practice. We report the study design and baseline patient characteristics.Methods XASSENT (NCT02558465) is an open-label, prospective observational, post-marketing surveillance cohort study in patients receiving rivaroxaban treatment for VTE. Enrolment took place between November 2015 and March 2018. XASSENT will follow patients for up to 2 years. Primary outcome variables: major bleeding and symptomatic recurrent VTE. Statistical analyses are exploratory and descriptive.Results Baseline patient characteristics at June 2020 (n = 2,299) are presented (58.2% female; mean age 66.7 years; mean weight 60.9 kg). The population encompasses patients with wide-ranging characteristics including older age, low weight, and renal dysfunction. Most participants (67.6%) had a history of VTE risk factors at baseline. Half of the population (50.4%) had DVT only; 41.4% had DVT with PE; 8.2% had PE only. Overall, 68.4% were inpatients and 77.1% had symptomatic VTE. Rivaroxaban was prescribed for initial treatment in 84.6% of patients and maintenance treatment in 15.4%. Most were prescribed the approved dose of rivaroxaban for initial (30 mg daily; 84.4%) or maintenance (15 mg daily; 81.9%) treatment of VTE in Japan. The most common reason for selecting non-recommended dose was ‘elderly’.Conclusions Results from XASSENT will complement phase 3 trial data and inform clinical practice.
Keywords: Japan; pulmonary embolism; rivaroxaban; venous thromboembolism; venous thrombosis